Lao PDR - Production Forestry Policy : Status and Issues for Dialogue, Volume 1. Main Report - World Bank (Washington, DC, 2013)
Forestry contributes 7-10 percent of Lao Gross Domestic Product (GDP) and 15-20 percent of non-agricultural GDP. In rural areas forest exploitation is one of the few available economic activities, and non-timber products provide more than half of family income. The sector contributes 34 percent of total export value, and even more of net foreign exchange. Forestry royalties as a share of government revenues have decreased from 20 percent in the mid-1990s to 6 percent of tax revenues and 5 percent of all revenues last year. Collection rates are low, around 50 percent, and royalty revenues have been declining since mid-1990s. Over the last five years, Treasury has realized only about one-third of the estimated market value of the timber harvested. Current wood industries' capacity exceeds long-term sustainable AAC, and despite heavy investment, their performance has not met expectations. There is no evidence that wood production has had a positive impact on rural poverty; rather it has had a negative one by destroying the environment on which the poor depend. This report concludes that fundamental problems in the forest policy framework can, and must be corrected for forestry to make its full contribution to national development. This Review focuses on proposing a narrow and select set of priority policy and implementation initiatives: improving production forest management and utilization, community participation in forest management, and controlling illegal logging. With interlinked and mutually reinforcing efforts in these areas, the production forestry sub-sector could be put on a sustainable path, greatly enhancing prospects or success in biodiversity conservation, watershed management and upland rural development. The blend of policy institutional and investment action needed, and priority for implementation is indicated in the attached summary Forest Policy Matrix and Proposed Action Plan.